Pengaruh Literasi Keuangan, Sikap Keuangan, dan Penggunaan Software Sistem Informasi Akuntansi Terhadap Kinerja UMKM - Fikriadi, Ilham; Herawansyah, Herawansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The purpose of this study was to examine how financial literacy, financial attitudes, and the use of accounting information system software impact the performance of MSMEs in Bengkulu City. Although small and medium enterprises (MSMEs) play a significant role in the national economy, they still face a number of challenges in financial management and the use of accounting technology. The study sample consisted of 78 MSMEs selected based on specific criteria through a purposive sampling technique. Primary data was obtained through the use of Google Forms and then analyzed using multiple linear regression using SPSS version 29. The results showed that financial attitudes positively and significantly influenced MSME performance. Conversely, financial literacy and the use of accounting information system software did not have a significant impact. These findings indicate that although MSMEs have good financial literacy, knowledge alone is not enough to improve performance without good financial attitudes. Due to a lack of technical understanding and a lack of application in business practices, the use of accounting software remains suboptimal. Collectively, the three variables successfully explained 52.7% of the variation in MSME performance, while other variables not included in the research model influenced the remainder. It is hoped that this research will provide real benefits for MSMEs, the government, and related institutions in creating strategies to improve business performance and encourage the optimization of financial digitalization in the MSME sector.